A166: Evaluation of Quality Indicators and Disease Damage in Childhood‐Onset Systemic Lupus Erythematosus Patients. Issue 11 (March 2014) - Harris, Julia G.; Maletta, Kristyn I.; Kuhn, Evelyn M.; Olson, Judyann C.
Abstract : Background/Purpose: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that can affect virtually every organ system and may lead to significant morbidities. A recent publication identified quality indicators specific to childhood‐onset SLE (cSLE) based on scientific evidence and expert opinion. Our study measured compliance with certain quality indicators and assessed organ‐specific dysfunction in our cSLE population using a validated damage index, which will help define a baseline for which to optimize management and focus treatment to control the underlying disease and prevent adverse effects of therapy. Methods: A retrospective chart review was performed on patients diagnosed with SLE prior to age 18 who were followed in the Children's Hospital of Wisconsin Rheumatology Clinic for at least one year between January 1999 and August 2012. The Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index was calculated to assess for chronic damage. Results: Analysis was performed on 75 patients with mean disease duration of 4.55 years. Eighty‐four percent of patients were female, 38.7% were black, 14.7% were Hispanic, and mean age of diagnosis was 13.2 years. The proportion of patients for whom care met the proposed quality indicators include: hydroxychloroquine use 94.6%, discussion of cardiovascular risk factors 17.3%, bone mineral density testing 26.7%, Vitamin D recommendation 81.3%, ophthalmologic examination 49.0%, influenza vaccination 70.3%, pneumococcal vaccination 25.3%, and meningococcal vaccination 47.2%. Disease damage was present in 41.3% of patients with average overall damage index score of 0.81. The most common entities leading to a damage score were cataracts, avascular necrosis, and diabetes. There was an association of disease damage at last follow‐up with minority race (p = 0.008) and with presence of vitamin D recommendation (p = 0.005). On the contrary, there was no statistical significance relating disease damage to lupus nephritis, age at diagnosis, body mass index, hydroxychloroquine use, or discussion of cardiovascular risk factors. Conclusion: Baseline application of proposed quality indicators in our cSLE population is varied ranging from 17.3% to 94.6%. This data is important to standardize care and target certain domains of disease management for improvement such as education and vaccination. The three most common areas of damage in our study may be related to corticosteroid use. This knowledge of organ‐specific damage is important to help identify at‐risk patients to optimize care and focus quality improvement efforts.